2019
DOI: 10.1186/s13033-019-0291-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems both precede and follow bullying among adolescents and the effects differ by gender: a cross-lagged panel analysis of school-based longitudinal data in Vietnam

Abstract: Background The significant psychosocial harms from bullying among adolescents create major challenges for mental health promotion programs and services in schools. While the negative consequences of bullying victimisation are well known, to date there is scarce empirical analysis of inverse associations, in which mental health problems make children more vulnerable to bullying victimisation and perpetration. Based on a short-term longitudinal study among adolescents in Vietnam, this study examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 43 publications
(58 reference statements)
3
31
0
1
Order By: Relevance
“…Our study echoed the previous findings that bullying experience was a widespread phenomenon among adolescents in the metropolitan area of Vietnam [21,31]. In our study, more than one-third (37.5%) of adolescents were involved in at least one type of bullying in the last three months.…”
Section: Plos Onesupporting
confidence: 90%
See 4 more Smart Citations
“…Our study echoed the previous findings that bullying experience was a widespread phenomenon among adolescents in the metropolitan area of Vietnam [21,31]. In our study, more than one-third (37.5%) of adolescents were involved in at least one type of bullying in the last three months.…”
Section: Plos Onesupporting
confidence: 90%
“…The findings of this study contributed to the current literature about the effects of different types of bullying on students' HRQOL and mental health. Prior studies showed that having bullying victimization experience increased significantly the risk of depression as well as suicidal ideation [21,49,50]. In this study, regarding HRQOL, we found that physical bullying had the strongest influence compared to other types of bullying, which might be because this type of bullying affects at least four (mobility, self-care, usual activity, and pain/discomfort) out of five dimensions of the EQ-5D-5L instrument.…”
Section: Plos Onementioning
confidence: 46%
See 3 more Smart Citations